University Library Buildings in Turkey: A Survey and a Case Study of Yildiz Technical University Main Library Building - Balanlı, Ayşe; Öztürk, Ayşe; Vural, Müjdem S.; Küçükcan, Berrin (Elsevier, 2007)
Balanli et al discuss the factors hindering university libraries in Turkey to develop. These include a high level of decentralization to multiple campuses and/or faculty libraries, the appointment of senior academics without library qualifications as library directors, lack of trained staff, extremely small collections of monographs and serials by international standards, and grossly varying and inadequate budgets.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: INFORMATION SCIENCE & LIBRARY SCIENCE, Turkey, Library resources; Social conditions & trends, Academic libraries; Universities and colleges, University and college libraries, Case studies